Personalized three-dimensional printed breast model for quantitative assessment of breast density using magnetic resonance imaging - Sindi, Rooa; Sun, Zhonghua (The Australasian Medical Journal pty ltd., 2020)
Three-dimensional (3D) printing has become an increasingly developed technique in the medical field and has been used in many clinical applications. Research has consistently shown that 3D-printed models derived from patient’s imaging data can serve as valuable tools for examining different breast-MRI protocols, testing radiofrequency coils, and evaluating system performance. This editorial highlights the utility of personalized 3D-printed breast model for the quantitative breast density assessment using MRI. A personalized 3D-printed breast model was developed and fabricated using silicone and peanut oils to mimic the MR-associated properties of fibroglandular and adipose breast tissues. The silicone and peanut oils’ T1 relaxation times were correspondingly determined on a 3T MRI system and linked to the tissue reference values.